Ilung: Interactive Holographic Medical Application for Lung CT Scans Using Hololens - Al Khayer, Aala; Indriasari Mansor, Evi (International Journal of Engineering and Technology, 2018)
This research aims to design a holographic medical application for lung CT scans using Microsoft HoloLens. iLung application offers users the possibility to interact with the actual lung of a patient in a mixed reality and 3D environment. A prototype of the iLung was developed based on raw CT scans data and converted into 3D model generation. This paper reports the earlier stage in designing the application. Based on the application’s overview with a group of users, the findings gathered showed that iLung prototype facilitates interactive manipulation and exploring of the 3D lung object. Feedback and comments were recorded for future improvements such as air taping interaction method and voice command.